Розвиток малого і середнього підприємництва як стратегічний напрям повоєнної відбудови сільських територій - Ластовченко, Павло Володимирович; Lastovchenko, Pavlo (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2025)
В статті розглянуто роль розвитку малого і середнього підприємництва (МСП) як стратегічного напрямку повоєнної відбудови сільських територій. Окрему увагу приділено аналізу ключових проблем, з якими стикаються підприємці у сільській місцевості, таких як обмежений доступ до фінансування, недостатня інфраструктура та низький рівень кваліфікації місцевих кадрів. Пропонуються конкретні рішення для стимулювання розвитку МСП, серед яких створення пільгових кредитних програм, підтримка інфраструктурних ініціатив, розвиток кооперацій та кластерів, а також впровадження інноваційних технологій. Підкреслена необхідність розвитку інновацій у сфері сільського господарства та агропереробки, що дозволить підвищити конкурентоспроможність місцевих підприємств. Впровадження новітніх технологій, зокрема в сфері енергоефективності, екологічного виробництва та переробки відходів, стане важливим фактором для сталого розвитку МСП. Дослідження показує, що малий і середній бізнес є потужним інструментом економічної трансформації сільських територій, сприяючи їх соціально-економічному повоєнному відновленню. The article analyzes the current state of development of small and medium-sized enterprises (SMEs) in rural areas, identifies the main challenges faced by entrepreneurs, and proposes comprehensive solutions to overcome them. The primary obstacles hindering the development of SMEs in rural areas include limited access to financing, underdeveloped infrastructure, low qualification levels of local personnel, and insufficient support from the state and local government authorities. At the same time, rural entrepreneurs encounter limited opportunities to create competitive products and access new markets, which significantly complicates the process of business recovery and development. To address these barriers, several key support mechanisms are proposed: the creation of preferential credit programs and grants for small businesses, the expansion of microcredit opportunities, and the introduction of state guarantees for loans to reduce financial risks. The article highlights the necessity of fostering innovation in agriculture and agro-processing, which would enhance the competitiveness of local enterprises. The implementation of modern technologies, particularly in the areas of energy efficiency, sustainable production, and waste processing, is deemed crucial for the sustainable development of SMEs. Additionally, it is important to develop export channels for rural businesses, which will ensure market expansion and increase entrepreneurs' incomes. Overall, the development of small and medium-sized enterprises in rural areas holds significant potential for socio-economic stabilization at the local level. Creating favorable conditions for SMEs through state support, infrastructure development, training, and innovation will not only facilitate the economic recovery of rural areas but also ensure their sustainable growth in the context of post-war reconstruction. Implementing the proposed measures will lay the foundation for establishing a strong economic base for rural communities, enabling them to effectively adapt to changes and ensure a high standard of living for their residents
Development of small and medium enterprises as a strategic direction for the post-war reconstruction of rural areas
Keywords: малий бізнес; small business; середній бізнес; medium-sized business; економічний розвиток; economic development; сільські території; rural areas; підприємництво; entrepreneurship; регіональна політика; regional policy; підтримка бізнесу; business support